2012
DOI: 10.1002/srin.201200016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laves Phase Precipitation and Coarsening on High‐Temperature Strength of Ferritic Stainless Steels

Abstract: Downsizing trends in the design of internal combustion engines require ferritic steels with greater strength at elevated temperatures. One method of improving the hightemperature strength is precipitation hardening with intermetallic phases such as the Laves phase. Thermodynamic calculations show, that the elements Nb and Si contribute to the Laves phase formation strongly. In this work, the influence of intermetallic precipitates on the mechanical properties of three different ferritic Fe-Cr stainless steels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Sim et al [11] also reported a rapid coarsening rate of Laves phase precipitates at high temperatures (700 °C). These precipitates coarsen rapidly and their contribution to precipitation hardening is comparatively small, although they inhibit grain growth and thus stabilize the microstructure [9]. However, coarse Laves phase precipitates on the grain boundaries can have a detrimental effect on the toughness of these steels [12].…”
Section: Influence Of the Alloying Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sim et al [11] also reported a rapid coarsening rate of Laves phase precipitates at high temperatures (700 °C). These precipitates coarsen rapidly and their contribution to precipitation hardening is comparatively small, although they inhibit grain growth and thus stabilize the microstructure [9]. However, coarse Laves phase precipitates on the grain boundaries can have a detrimental effect on the toughness of these steels [12].…”
Section: Influence Of the Alloying Elementsmentioning
confidence: 99%
“…Due to the low stability of M 23 C 6 in low-carbon ferritic steels at higher temperatures, this phase can be excluded (Figure 3a). In previous works the influence of Laves phase in ferritic stainless steels during long-term annealing was investigated [9]. An analysis of the microstructure in different states annealed at 900 °C showed that the Laves phase precipitates grow and rapidly coarsen.…”
Section: Influence Of the Alloying Elementsmentioning
confidence: 99%
“…From the literature [19] and our previous investigations, Nb is known to be the most potent Laves phase former and its strong effect can be enhanced by combining it with Si. [20] However, low concentrations of C and N, which are unavoidable during steel production, decrease the solvus temperature of the Laves phase due to the high affinity of Nb for C and N, thus leading to the formation of carbides/nitrides instead of the Laves phase. [21] Microalloying with Ti minimizes primary precipitation of niobium nitrides and niobium carbides, so that this element is still available for Laves phase formation.…”
Section: A Alloy Designmentioning
confidence: 99%
“…This leads to the conclusion that a stable Laves phase content of about 1 vol% at service temperature could effectively retard grain coarsening . Thus, systematic formation of the Laves phase in addition to solid‐solution hardening may lead to a new way of enhancing the high‐temperature strength of heat‐resistant ferritic steels …”
Section: Introductionmentioning
confidence: 99%
“…This work investigates the influence of the Laves phase and grain size on strength, toughness, and ductility at room temperature. Three previously developed steels of the system Fe‐Cr‐Nb(‐Al) (designated Fe18CrW, Fe18CrMoW, and Fe19CrWAl) are the basis of this investigation. These steels are designed to contain about 1 vol% Laves phase at 900°C, and their high‐temperature strength is enhanced by alloying with Nb, W, and/or Al .…”
Section: Introductionmentioning
confidence: 99%